Divergent Perceptions of Peace in Post-Conflict Societies: Insights from Sri Lanka. (October 2022) - Carey, Sabine C.; González, Belén; Gläßel, Christian
Research on postwar peace focuses primarily on how elites and institutions can prevent relapse into civil war. In line with this special issue's focus on citizens' experiences, we take a micro-level approach to explore peace beyond the absence of war. We investigate how members of opposing sides experience peace a decade after a decisive victory of the majority. Using original survey data from a representative sample of 2000 respondents in 2018 Sri Lanka, we find that even one decade after the conflict members of the Sinhalese winning majority are consistently more likely to report improvements in peace than Tamils, who were represented by the defeated minority. But the benefit of a "victor's peace" does not seem to translate into an optimistic outlook of the victorious group, nor does it increase people's endorsement for repressive state measures. Despite the drastically improved physical security for the defeated ethnic minority since the war, they experience a deterioration in other dimensions of peace. Our findings have important implications for a deeper understanding of variations in peace and reconciliation processes.